Adaptive Informal Food Commons (AIFC): A New Economic Theory of Community-Based Flexibility in Addressing Hunger in Developing Countries - Reuveni, Saada (Technium Social Sciences Journal, 2026)
Hunger in developing countries persists despite the expansion of markets, state welfare, and international aid. Traditional economic theories explain food access through price mechanisms, institutional capacity, or formal safety nets, yet they overlook the everyday reality that millions rely on informal, community-based systems to survive. These systems-food sharing, reciprocal support, rotating credit groups, communal storage, and flexible vendor networks-operate outside official structures but provide critical resilience during shocks. This paper introduces a new theoretical model: Adaptive Informal Food Commons (AIFC). AIFC conceptualizes how communities dynamically coordinate food access through shared resources, non-monetary value exchange, social norms, and trust-based distribution. Unlike static welfare programs, these commons are fluid, decentralized, and capable of rapid adaptation to climate events, price volatility, and institutional failure. Drawing on literature synthesis and illustrative cases, the paper argues that AIFCs represent a third economic pillar of food security-distinct from state and market-and function as “shadow safety nets” that redistribute risk and sustain livelihoods. By theorizing their mechanisms, this framework fills a major gap in economic thought and provides a foundation for new policy approaches that support, rather than disrupt, informal resilience. The paper concludes with a research agenda for empirically modeling AIFCs and integrating them into global hunger strategies.